FORMATION OF HEALTHY LIFESTYLE OF STUDENTS IN THE PROCESS OF INDEPENDENT WORK ON THE COURSE OF "PHYSICAL EDUCATION" (Pedagogy of Higher and Secondary Education, 2009)
The is a theoretical analyses of the researches of the students problem on physical bringing.